Study of Soil Chemical Properties on Palm Oil Productivity in PT. Gemilang Sejahtera Abadi in East Kalimantan - Christian, Bertolomius Medy; Munir, Mochammad; Wicaksono, Kurniawan Sigit (JOURNAL OF TROPICAL SOILS, 2024)
East Kalimantan is a region that contributes to palm oil production. Industrial development in the area still needs to be improved in some plantations because there is a limiting palm oil productivity. This study examined the chemical properties of the soil on the PT. Gemilang Sejahtera Abadi (GSA) plantation. Observations were made in four fields with the same variety but different productivity levels. Correlation analysis and simple linear regression were used to identify factors influencing productivity. The soil on the plantation land was dominated by Typic Hapludults soil type, included in the Ultisols order. The highest productivity was found in Afdeling 1, 2, and 5, while the lowest was in Afdeling 4. The pH in each afdeling was classified as acidic, and the Organic-C, N, and base saturation contents were low. The CEC in afdeling 1 and 2 was classified as medium, while in afdelings 4 and 5 was low. All correlation analyses showed a positive relationship between the variables and palm oil productivity, with low correlation coefficients for pH, organic-C, N, P, and base saturation. The correlation coefficient between CEC and palm oil productivity has a strong relationship.